Direct Photolithography of WOx Nanoparticles for High-Resolution Non-Emissive Displays - Gu, Chang; Yang, Guojian; Wang, Wenxuan; Shi, Aiyan; Fang, Wenjuan; Qian, Lei; Hu, Xiaofei; Zhang, Ting; Xiang, Chaoyu; Zhang, Yu‑Mo (Nano-Micro Letters, 2024)
High-resolution non-emissive displays based on electrochromic tungsten oxides (WOx) are crucial for future near-eye virtual/augmented reality interactions, given their impressive attributes such as high environmental stability, ideal outdoor readability, and low energy consumption. However, the limited intrinsic structure of inorganic materials has presented a significant challenge in achieving precise patterning/pixelation at the micron scale. Here, we successfully developed the direct photolithography for WOx nanoparticles based on in situ photo-induced ligand exchange. This strategy enabled us to achieve ultra-high resolution efficiently (line width < 4 µm, the best resolution for reported inorganic electrochromic materials). Additionally, the resulting device exhibited impressive electrochromic performance, such as fast response (< 1 s at 0 V), high coloration efficiency (119.5 cm2 C−1), good optical modulation (55.9%), and durability (> 3600 cycles), as well as promising applications in electronic logos, pixelated displays, flexible electronics, etc. The success and advancements presented here are expected to inspire and accelerate research and development (R&D) in high-resolution non-emissive displays and other ultra-fine micro-electronics. Highlights: 1 Direct photolithography of electrochromic WOx nanoparticles via in situ photo-induced ligand exchange is proposed and demonstrated. 2 The highest resolution among inorganic electrochromics (< 4 µm) is achieved, which is promising in high-resolution non-emissive displays. 3 The as-prepared device exhibits highly remarkable performance including rapid response, high coloration efficiency and durability.